Determining Proton Transport in Pseudo Catalyst Layers Using Hydrogen Pump DC and AC Techniques. Issue 8 (25th May 2020) - Sabarirajan, Dinesh C.; Liu, Jiangjin; Qi, Yongzhen; Perego, Andrea; Haug, Andrew T.; Zenyuk, Iryna V.
Abstract : Optimizing electrode morphology with a more uniform ionomer distribution is key to reducing ohmic losses and increasing electrocatalyst utilization in polymer electrolyte fuel cells (PEFCs). Inherent ionomer conductivity, volume fraction and tortuosity determine effective ionic conductivity. We use hydrogen pump (HP) method to measure effective ionic conductivity of a pseudo catalyst layer (PCL) comprised of Vulcan XC-72 carbon black and 3M 825 EW ionomer with ionomer to carbon (I/C) ratios of 0.6, 1 and 1.4 and relative humidity (RH) range of 50 to 120%. These direct current (DC) experiments are then compared with electrochemical impedance spectroscopy (EIS). Both DC and EIS methods show good agreement, indicating that EIS can be used as an alternative to DC method in HP experiment. Ionic conductivity for PCL with I/C of 1 and 1.4 was found to be about one order of magnitude higher than I/C of 0.6 for most of the RH range. At 90% RH tortuosities for I/C = 1 and 1.4 were close to 1, whereas tortuosity for I/C = 0.6 was 3. With decrease in relative humidity tortuosities increased linearly and at 50% relative humidity a PCL with I/C = 0.6 had the highest tortuosity of 6.1.